2021
DOI: 10.1186/s40478-021-01282-8
|View full text |Cite|
|
Sign up to set email alerts
|

High diagnostic performance of independent alpha-synuclein seed amplification assays for detection of early Parkinson’s disease

Abstract: Alpha-synuclein seed amplification assays (αSyn-SAAs) are promising diagnostic tools for Parkinson’s disease (PD) and related synucleinopathies. They enable detection of seeding-competent alpha-synuclein aggregates in living patients and have shown high diagnostic accuracy in several PD and other synucleinopathy patient cohorts. However, there has been confusion about αSyn-SAAs for their methodology, nomenclature, and relative accuracies when performed by various laboratories. We compared αSyn-SAA results obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
138
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 132 publications
(146 citation statements)
references
References 55 publications
8
138
0
Order By: Relevance
“…The research and development (R&D) kinetic αS-SAA was utilized to analyze CSF samples and brain tissues. The methods of the kinetic αS-SAA have been reported in detail elsewhere 21, 22 . Briefly, CSF samples and brain homogenates (BHs) were evaluated in triplicates (40µL/well) in a 96-well plate (COSTAR 96, cat# 3916), in a reaction mix consisting of 0.3mg/ml rec-αSyn (Amprion, cat# S2021), 100mM PIPES pH 6.50 (Sigma, cat# 80635), 500mM NaCl (Lonza, cat# 51202), 10µM ThT (Sigma, cat# T3516), and a 3/32-inch BSA-blocked Si 3 N 4 bead (Tsubaki Nakashima).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research and development (R&D) kinetic αS-SAA was utilized to analyze CSF samples and brain tissues. The methods of the kinetic αS-SAA have been reported in detail elsewhere 21, 22 . Briefly, CSF samples and brain homogenates (BHs) were evaluated in triplicates (40µL/well) in a 96-well plate (COSTAR 96, cat# 3916), in a reaction mix consisting of 0.3mg/ml rec-αSyn (Amprion, cat# S2021), 100mM PIPES pH 6.50 (Sigma, cat# 80635), 500mM NaCl (Lonza, cat# 51202), 10µM ThT (Sigma, cat# T3516), and a 3/32-inch BSA-blocked Si 3 N 4 bead (Tsubaki Nakashima).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, αSyn Seed Amplification Assays (SAAs), such as protein misfolding cyclic amplification (PMCA) and real time quaking induced conversion (RT-QuIC), have been adapted to detect misfolded αSyn aggregates (αSyn seeds) in CSF and peripheral tissues with remarkable diagnostic accuracy 15-20 . αSyn-SAA in CSF of clinically diagnosed PD and DLB patients has shown impressive results, with several independent groups reporting sensitivities and specificities near or above 90% 15-17, 21, 22 . However, detailed studies of αSyn-SAA performance in neuropathologically validated cohorts with varying distribution of LRP and clinical diagnoses other than LB disease are rare 23 .…”
Section: Introductionmentioning
confidence: 99%
“…This protocol allowed much more rapid detection of seeds within 1–2 days (vs. 5–13 days for the prior αSyn RT-QuIC and PMCA assays), and initial testing of CSF samples from PD and DLB cases showed similarly high sensitivity (92 and 94%) and an overall specificity of 100%. Further testing of larger and broader CSF panels from PD ( Manne et al, 2019 ; Rossi et al, 2020 ; Orru et al, 2021 ; Russo et al, 2021 ), DLB, iRBD, and PAF patients gave sensitivities between 93and 100% and specificities between 84 and 98% ( Rossi et al, 2020 ). As with the Green assay, the Groveman assay failed to detect αSyn seeds in CSF from most MSA cases, consistent with MSA seeds being conformationally distinct from those Lewy body disorders.…”
Section: Synucleinopathiesmentioning
confidence: 98%
“…While batch-to-batch variations in aSyn are recognized as a possible source of variation in the field [ 28 , 29 ], only a subset of studies reports systematic comparison of inter-batch variability [ 28 , 30 , 31 , 32 ]. In a recent study, SAAs were performed on control- and PD CSF by three independent groups in parallel according to their respective protocols [ 33 ]. The study confirmed the high diagnostic value of SAAs: PD was diagnosed with a sensitivity of 86–96% and specificity of 93–100% but reported high variability with regards to assay parameters (AUC maximum fluorescence, time to threshold) measured.…”
Section: Putative Diagnostic Assays Based On Asyn Seeding and Aggrega...mentioning
confidence: 99%